Synthesis of o-methyl trifluoromethyl sulfide substituted benzophenones via 1,2-difunctionalization of aryne by insertion into the C-C bond - Ahire, Milind M.; Khan, Ruhima; Mhaske, Santosh B. (Organic Letters, 2017)
An efficient process for the preparation of valuable o-methyl trifluoromethyi sulfide substituted benzopheriones has been developed. The transition-metal-free method features insertion of aryne into a C-C sigma-bond under mild reaction conditions for the first time to achieve ortho-difunctionalized arenes containing a pharmaceutically important trifluoromethylthio functional group. A wide substrate, scope has been demonstrated for the developed protocol.

Synthesis of succinimide derivatives by NHC-catalyzed stetter reaction of aromatic aldehydes with N-substituted itaconimides - Ahire, Milind M.; Mhaske, Santosh B. (ACS Omega, 2017)
An N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aromatic aldehydes with N-substituted itaconimides has been developed. A delicate balance between the Stetter reaction and the competing isomerization of the itaconimide double bond has been achieved in this operationally simple reaction to afford valuable new succinimide derivatives containing 1,4 and 1,5 dicarbonyl scaffolds in good to excellent yields. The reaction tolerates variable substituents on both aldehydes and N-substituted itaconimides.

Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.